ANALISIS KETERBUKAAN INFORMASI PUBLIK DALAM KAJIAN TEORI HAK ASASI MANUSIA DAN EFEKTIVITAS HUKUM - Toni Toni (PROGRESIF: Jurnal Hukum, 2017)
The openness of public information is part of the human rights related to personal development rights guaranteed in legislation. This study was conducted to find out the legal events when examined from the theory of human rights and the effectiveness of the law. The results of this study are openness of public information is a human right is not supernatural guaranteed in the basic law and the rules of corporate governance and implementation in the field has not been fullest because it influenced several factors namely: the difference between the understanding of perception public body with the applicant information public body that held the rule of State secrets and the lack of synchronization between the standards and regulations of public information disclosure with State secrets.